2013
DOI: 10.5367/ihe.2013.0143
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Entrepreneurial Activity at Cape Town and Stellenbosch Universities, South Africa

Abstract: Entrepreneurial activity at universities, especially spin-off formation, has emerged as an important mechanism for accelerating the transfer of technology and knowledge to commercial markets. With some exceptions, such as China, studies on university entrepreneurship have tended to concentrate on the experiences of developed countries. Perhaps because of the lack of a comprehensive database of university spin-offs, studies on experience in South Africa have typically included spin-offs only as part of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Chiesa and Piccaluga (2000), for example, in their research on Italian spin-offs, found that the majority of the founders' motivations (nearly 60%) were pull factors such as identifying market opportunities and applying their knowledge to practical applications. Jafta and Uctu (2009) found similar rankings of motivations for the Western Cape university spin-off firms in South Africa. Kondo (2004) conducted a first survey on the university spin-off companies in Japan and found that the primary motive in founding a company is to put invented technologies to practical use.…”
Section: Asian Journal Of Technology Innovationsupporting
confidence: 70%
“…Chiesa and Piccaluga (2000), for example, in their research on Italian spin-offs, found that the majority of the founders' motivations (nearly 60%) were pull factors such as identifying market opportunities and applying their knowledge to practical applications. Jafta and Uctu (2009) found similar rankings of motivations for the Western Cape university spin-off firms in South Africa. Kondo (2004) conducted a first survey on the university spin-off companies in Japan and found that the primary motive in founding a company is to put invented technologies to practical use.…”
Section: Asian Journal Of Technology Innovationsupporting
confidence: 70%
“…As already noted, the main reason given was lack of funding, followed by commercialization, distribution and estimation of market demand. Jafta and Uctu (2009) found support for the significant role played by funding in this decision in earlier research on spin-offs. They examined the major problems that spin-off companies encountered at two South African universities and found that, apart from funding, factors such as recruiting skilled people, a lack of facilities, the task of marketing the developed products and time constraints all played a part in deterring the spin-off decision (Jafta and Uctu, 2009).…”
Section: Factors Affecting the Decision Not To Set Up A Companymentioning
confidence: 76%
“…Jafta and Uctu (2009) found support for the significant role played by funding in this decision in earlier research on spin-offs. They examined the major problems that spin-off companies encountered at two South African universities and found that, apart from funding, factors such as recruiting skilled people, a lack of facilities, the task of marketing the developed products and time constraints all played a part in deterring the spin-off decision (Jafta and Uctu, 2009). Furthermore, Kamariah et al (2011) and Nelsen (2007) point out that university-generated technologies are often still at an embryonic stage and will require substantial investment of time, money and skills to be made market-ready.…”
Section: Factors Affecting the Decision Not To Set Up A Companymentioning
confidence: 76%
See 1 more Smart Citation
“…Another important indicators is to look at the number of start-ups created by the universities. University spin-offs (also called university entrepreneurship, academic spin-offs and academic entrepreneurship) has been studied by many researchers in South Africa (see for instance Jafta and Uctu, 2013;Rorwana and Tengeh, 2015;Urban and Chanston, 2019) and is seen as an important factor that promotes innovation.…”
Section: An Overview Of Ttos' Performance In South Africamentioning
confidence: 99%